2019
DOI: 10.1029/2019jb017405
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Isotope Constraints on Recycled Oceanic Crust in the Mantle Sources of the Emeishan Large Igneous Province

Abstract: Identification of the nature of recycling crustal materials in the sources of large igneous provinces (LIPs) is crucial for understanding compositional heterogeneity of the deep mantle. To provide new constraints on this issue, here we reported high‐precision zinc isotope data on picritic and basaltic lavas from the Emeishan LIP, SW China. Using olivine‐melt Mg‐Fe equilibrium and log (incompatible elements)‐log (MgO) systematics, the parental magma of picritic lavas is estimated to have a MgO content of 21.8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 98 publications
1
15
0
Order By: Relevance
“…The δ 26 Mg values of the studied alkali basalts (−0.44 ± 0.03‰ to −0.33 ± 0.02‰) are detectably lower than those of the mantle (−0.25 ± 0.04‰) and, thus, unable to have been caused by partial melting or fractional crystallization. Zinc isotopes may be fractionated during crystal‐melt differentiation involving olivines that are isotopically lighter than the melts (McCoy‐West et al, 2018; Sossi et al, 2015; Yang & Liu, 2019), but detectable fractionation (~0.1‰) only occurs at the very end of the differentiation sequence when MgO falls below 3 wt.% as observed in the Kilauea Iki lavas (Chen et al, 2013). The studied alkali basalts have near‐primary compositions (MgO = 8.7–12.2 wt.%) and have δ 66 Zn values above the trend of Kilauea Iki lavas (Chen et al, 2013) as well as of global OIBs (Beunon et al, 2020; Wang et al, 2017) (Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
“…The δ 26 Mg values of the studied alkali basalts (−0.44 ± 0.03‰ to −0.33 ± 0.02‰) are detectably lower than those of the mantle (−0.25 ± 0.04‰) and, thus, unable to have been caused by partial melting or fractional crystallization. Zinc isotopes may be fractionated during crystal‐melt differentiation involving olivines that are isotopically lighter than the melts (McCoy‐West et al, 2018; Sossi et al, 2015; Yang & Liu, 2019), but detectable fractionation (~0.1‰) only occurs at the very end of the differentiation sequence when MgO falls below 3 wt.% as observed in the Kilauea Iki lavas (Chen et al, 2013). The studied alkali basalts have near‐primary compositions (MgO = 8.7–12.2 wt.%) and have δ 66 Zn values above the trend of Kilauea Iki lavas (Chen et al, 2013) as well as of global OIBs (Beunon et al, 2020; Wang et al, 2017) (Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
“…component in the Emeishan LIP (Tian et al, 2017). A Zn isotope study has also shown that the δ 66 Zn values of Emeishan picrites and basalts ranges from 0.24‰ to 0.34‰, which is not compatible with the presence of carbonatitic components in the sources of the Emeishan LIP, but may be the joint consequence of the addition of recycled oceanic crust and mantle melting (C. Yang & Liu, 2019).…”
Section: The Origin Of Em1 Signatures In Lijiang Melt Inclusionsmentioning
confidence: 98%
“…Recently, some studies have proposed that recycled materials in the Emeishan mantle plume played a key role in producing the observed compositional diversity of the Emeishan LIP (Bai et al., 2014; Hou et al., 2013; C. Yang & Liu, 2019; Yu et al., 2014; L. Zhang et al., 2019). C. Yang and Liu (2019) and L. Zhang et al. (2019) estimated an oceanic crust component of ∼15% in the source of the Emeishan LIP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the basalts from the MMT and MOT have MORB-like δ 66 Zn values with slightly higher δ 66 Zn values than those of the NMA, SMA, and SOT basaltic lavas (Figure 4). The δ 66 Zn values of the NMA, SMA, and SOT basaltic lavas fall within the range of the normal mantle (+0.18 ± 0.06 ‰, 2SD; Figure 4a; Doucet et al, 2020;Sossi et al, 2018; and are all lower than those of the global MORB (0.27 ± 0.05‰, 2SD; , ocean island basalts (OIB) (Beunon et al, 2020;Chen et al, 2013;, South China Sea basalts (0.22-0.31‰; Liao et al, 2020), the Kamchatka-Aleutian arc lavas , and East China basalts (Liu et al, 2016;Yang & Liu, 2019) (Figure 4a). The δ 66 Zn values of andesites and dacites from the Mariana and Ryukyu subduction zones also fall within the range of the normal mantle compared to those of the OT rhyolites (Figure 4b).…”
Section: Resultsmentioning
confidence: 88%